Propuesta de formación para la pastoral juvenil en la vicaría urbana del cantón Cuenca - Toledo Calle, Segundo Victor (2015)
This work has a "Training Proposal for Youth Pastoral in the Urban Vicariate of Canton Cuenca". Work which was prepared after an experience gained as a member of the Commission on Catechesis of the Vicariate in the periods between 2008 and 2012 where we saw the need for investigation and subsequent proposal to the Department of Pastoral Urban Vicariate. This work is divided into four chapters each routed towards the ultimate goal of the research is to have enough information and material that leads to the development of the final product. Each chapter seeks to clarify certain points or topics, beginning with Chapter I; This chapter seeks to define the meaning of Youth Pastoral, with reference to prominent authors who from their experience they explain and routed to a new topic that is the Youth Pastoral in vocational key and accompaniment; knowing one's own Youth Pastoral work is precisely accompany the young towards achieving their life project. But not only the life project is important for youth work; this chapter also discusses topics such as dimensions, associative, cultural, vocational and faith; collaborating since its specificity to training and Pastoral work. Chapter II focuses his theory to training; revealing the importance of preparing pastoral workers in different subjects, to provide lessons required in later chapters. With the lighting of the elaborate topics; in Chapter III we find a detailed explanation of the methodology used for research; development of tools and finally the reference tables in which we rely to make decisions and subsequent proposal, In Chapter IV and with the data achieved is all the information obtained for study and subsequent achievement of the proposal; it has an analysis of strengths and weaknesses, four guides’ tables for routing activities and finally the proposed. As a major pastoral work, we end with conclusions and recommendations.